Assessment and Prognosis Aid Brought on by the Mensurable International Systems for the Attention of Patients Suffering from Neuroictus. - Rubén Bembibre Taboada; Carlos Jaime Geroy Gómez; Miguel Angel Buergo Zuaznábar; Diosdania Alfonso Falcón; Ariel Menéndez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: Assessment and prognosis aid brought on by the mensurable international systems recongized in the attention of patients suffering from neuroictus has its success and mistakes. The emission of a prognosis which establishes a strategy for discapacity seems to be not to proceed with such instruments. In our country was created a system that compiles the above mentioned ratings which make viable to do a research which define the above postulates. Objective: To determine the advantages and disadvantages of the mensurable international systems. Methods: The international instrument system was implemented compiled in one system with 202 cases in a five-month period of time. A characterization of the serie was carried out and tests were applied to determine the correlation coefficient as well as significant statistics results when correlating the instruments wth the state of the patient at the moment of discharging according to Rankin scale. Results: A predominium of ischemic neuroictus of atherothrombosis type was verified in elderly. The discapacity generated by neuroictus was evident. The value in the assessment and the prognosis inference of some international instruments was shown. But there was evidence that they do not give the prognosis of the disability in a sub stratified way. Conclusions: The international measuring instruments in the nueroictus are not effective for the assessment and follow up of the patient. The contributed aid of these instruments in the prognosis emission is inferred and has limitations, so it will be commendable to create a more simple and unique predictable mensurable system.